Analisis Model Attention - Interest - Search - Action - Share terhadap Akun Instagram @bodatnation sebagai Media Baru Pemasaran - Theo Michael Hutapea (PERSPEKTIF, 2022)
The increasing number of internet users and the emergence of this new technology not only affect our lifestyle but also create new marketing strategies for product owners to promote and sell their products. In addition, social media also provides an easier way for product owners to understand their consumers. This study seeks to identify the AISAS communication model on the Instagram account @bodatnation in running a paid promotion business. The method used in this study is a qualitative research method with observation techniques, literature review, and in-depth interviews with the founder and admin of the @bodatnation Instagram account. The results of this study indicate that the Instagram account @bodatnation can adopt the AISAS communication model. The admin of the @bodatnation account has succeeded in finding issues and trends in society and then processing them into interesting and informative content. Point Search – Action – Share is very influential on consumers for purchasing decisions for products that are being promoted or using paid promote services.